Potassium fertilization and its residual effect on productivity and quality of potato tubers - Silva, Heider Rodrigo Ferreira; Fontes, Paulo Cezar Rezende (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to determine the optimal K dose and its residual effect on maximum yield and quality of potato (Solanum tuberosum) tubers. Experiment 1 was carried out in soil with low K content (38 mg dm‑3), in a randomized complete block design, with four replicates, whose treatments consisted of five K rates – 0, 110, 220, 440, and 880 kg ha‑1 K2O –, as KCl, applied in the grooves in the pre‑planting period. Experiment 2 was carried out in the same location, using the residual content of the fertilizer applied in experiment 1. Potassium fertilization and its residual effect significantly affected the number, yield, and dry matter of tubers. However, high doses of K reduced the dry matter content and the specific gravity of tubers. The residual K content did not affect all components of productivity. The maximum economic efficiency dose was 393.5 kg ha‑1 K2O, which gave 36.2 Mg ha‑1, in experiment 1, and 19.6 Mg ha‑1, in experiment 2, as the maximum yields of commercial tubers.